Cognitive-Locomotor Dual-Task Interference in Stroke Survivors and the Influence of the Tasks: A Systematic Review - Deblock-Bellamy, Anne; Lamontagne, Anouk; Blanchette, Andréanne K. (Frontiers in Neurology, 2020)
Background: Walking in the community can be challenging for stroke survivors. The fact that community walking often requires performing another task while walking further adds to this challenge and can lead to a deterioration of performance in one or both tasks. Objective: To review the existing literature about cognitive-locomotor dual-task interference (DTI) magnitude and pattern while walking in patients with stroke and to explore the influence of tasks’ nature on DTI. Moreover, this review investigated the differences in DTI between stroke survivors and age-matched healthy adults. Methods: The literature search was conducted in 4 databases (MEDLINE, CINAHL, EMBASE and PEDro). Two authors independently identified relevant studies based on predetermined selection criteria. Among these criteria, studies had to include both locomotor and cognitive DTI. Methodological quality of the studies was independently assessed by two raters using a standardized checklist. Studies were categorized according to the nature of the locomotor and the cognitive tasks. Results: A total of twenty studies, with good to high methodological quality, were selected. Task combinations, outcome measures and participants characteristics varied widely from one study to another. Despite heterogeneous results across studies, mutual DTI (decrements in both locomotor and cognitive performance) was the most frequently observed pattern in participants with stroke. Interestingly, this DTI pattern was systematically obtained when participants had to avoid obstacles while walking. DTI seemed also to be influenced by the nature of the cognitive task. Compared to age-matched healthy participants, stroke survivors had greater DTI. Mutual interferences were also more frequently observed in stroke survivors than in age-matched healthy adults. Conclusions: DTI magnitude and pattern in persons with stroke varied considerably across studies. Multiple factors, including nature of the tasks, may influence dual-task abilities when assessing individuals with stroke. Consequently, dual-task assessments should be performed in similar contexts of individuals’ daily lives to ensure ecological validity.